The self-care routine in undergraduate students during the Covid-19 pandemic (Research, Society and Development, 2024)
Introduction: Self-care for health represents much more than the individual's ability to “do things” themselves. The Covid-19 pandemic marked people with social distancing, changing people's daily lives and routines, thus bringing questions, concerns, and fear, making everything very unstable. Objective: To identify whether the self-care routine of undergraduate students has changed during the Covid-19 pandemic. Methodology: This is a study with a quantitative approach, descriptive in nature and cross-sectional. Students from the occupational therapy course at a state university in northeastern Brazil participated in this research. The study was done online, where a link was made available via email and WhatsApp with the questionnaire. In data collection, some questions were used for identification and, the Self-Care Capacity Assessment Scale - EACAC (ASA-A). We use a simple and descriptive analysis. Results/discussion: The overall result of the scale shows useful results, however in the individual questions there were significant points to be mentioned. The students didn’t have a self-care routine, with food, sleep, and time for themselves being the most affected areas. Conclusion: The Covid-19 pandemic caused changes in students' self-care routines. Although these students did not need to travel to the University due to the virtualization of classes, they couldn’t establish a plan to develop a satisfactory self-care routine.